INVESTIGATING STUDENTS’ LEARNING DIFFICULTIES IN INTEGRAL CALCULUS - Ferrer, Flordeliza P. (PEOPLE: International Journal of Social Sciences, 2016)
The study aims to investigate the students’ learning difficulties in Integral Calculus, specifically in calculating integrals. The mixed methods research design was employed to gather quantitative data from the students’ answers in the examination and collect qualitative data from them through open-ended interviews and scrutiny of their solutions. Findings of related previous investigations were documented to understand more the nature of the difficulties in the subject as experienced by others. Participants of the study were given the examination in indefinite integrals composed of items that require solely the use of integration formulas and items in which integration techniques should be applied. The quantitative data disclosed, after subjecting the index of difficulties to statistical treatment, that the learners have experienced the same level of difficulties in dealing with the two types of integrals. The qualitative data revealed, as viewed by the participants and as reflected in their solutions, that many of the errors pertain more to the learners’ ability in trigonometric manipulation rather than with the integration per se. It was further concluded as highlighted from previous studies, that the learners’ difficulties in integration are evidently attributed to the inherent mathematical knowledge and skills acquired by the students from basic mathematics.